Adoption Of Online Banking - Shivam Khadelwal; Dr. Sandeep Shukla (Revista Electronica de Veterinaria, 2024)
This research examines the factors influencing consumer adoption of RuPay, an Indian electronic payment system launched by the National Payments Corporation of India (NPCI). The study uses a mixed-methods approach, focusing on demographics, transaction prices, merchant acceptance, awareness efforts, and security concerns. Results show that younger consumers and those with higher income levels are more likely to adopt RuPay due to lower transaction costs and increased merchant acceptance. The elimination of the Merchant Discount Rate has reduced transaction costs, encouraging merchants to accept the payment method. Awareness campaigns by the government and NPCI have increased consumer knowledge about RuPay's benefits, but gaps remain, especially in rural areas. Security concerns have not significantly deterred adoption, as most users feel confident in digital transactions.